Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources.  Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

Microlearning Resource: Changing How Services Are Delivered So Fewer Patients Come to Health Facilities in the Context of COVID-19 Pandemic | Global Financing Facility
In this learning object you will be able to: Explore the changes needed in service delivery to reduce the number of patients who go to health facilities. Identify good practices in terms of the role of Community Health Workers to provide services, use of digital and telemedicine services, and Family Planning modeling and use of private sector to deliver services. Reflect about possible required changes in participating countries’ health services.
Keywords: Health PEA; L - english / inglês; access to services / acesso a serviços; health - COVID-19 / saúde – COVID-19; health / saúde

Mozambique: Covid-19 triples in one week; mining beaches for white paint - Hanlon, Joseph (Mozambique)
New Covid-19 cases triple in one week New Covid-19 cases tripled in less than a week. This is clearly related to people ignoring preventive measures against Covid-19 during the festive season, the director of research at the National Health Institute (INS), Sergio Chicumbe, said Saturday. Crowds
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; GD - Xai-Xai; L - english / inglês; health - COVID-19 / saúde – COVID-19; health / saúde

Enfermeiras acusadas de cobranças ilícitas à parturientes em Chimoio - MMO (Mocambique Media Online, 2021)
Três enfermeiras de saúde materno-infantil afectas à maternidade do Hospital Provincial de Chimoio, estão a ser ouvidas pela procuradoria provincial de Manica indiciadas de cobranças ilícitas à parturientes.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde